METHODOLOGY OF WORKING WITH VOCABULARY IN PRIMARY SCHOOL NATIVE LANGUAGE AND READING LITERACY LESSONS (Scientific journal of the Fergana State University, 2024)
This article discusses the methodology of working with vocabulary in primary school native language and reading literacy lessons aimed at enhancing students' speech development, shaping literacy, enriching vocabulary, elevating speech culture, and acquiring flawless writing skills through the use of dictionaries.Developing students' speech is primarily related to enriching their vocabulary. Working on vocabulary is of great practical importance in increasing vocabulary. In the process of conducting vocabulary work on the studied text, students will learn old words, new words, words related to professions, words specific to the dialect, typical of the vocabulary of the language. they get acquainted with the words specific to the artistic style in a practical way.Vocabulary work should be carried out consistently both in native language classes and in reading classes. In general, teaching elementary school students the vocabulary of the language will increase their vocabulary, improve their speech culture, and make them become people who fully feel the great power, magic and charm of our national language provides.